Teaching Legal Problem Solving: A Problem-based Learning Approach Combined with a Computerised Generic Problem - Fiona Martin (Legal Education Review)
Providers of pre-admission practical legal training (PLT) aim to equip their graduates with a range of attitudes, skills, and strategies to enable them to function as ethical and competent newly admitted practitioners. In attempting to achieve those objectives, PLT providers need to try to gauge students’ intentions and perceptions in the learning process by considering how students approach learning, for this “has become one of the most significant and widely researched concepts in higher education. It is a central concept in the framework of teaching and learning law.” An important part of this “central concept” relates to students’ intentions in approaching a learning task – whether they intend to seek meaning and understanding from it, or merely to acquire what they perceive to be sufficient knowledge to complete part of a process. Consistently higher quality learning outcomes, more satisfactory results and increased student satisfaction have been linked to students adopting a “deep” approach to learning.